2017
DOI: 10.1080/14767058.2017.1397125
|View full text |Cite
|
Sign up to set email alerts
|

Is blood transfusion necessary in all patients with disseminated intravascular coagulation associated postpartum hemorrhage?

Abstract: According to the modified ISTH score, we found that blood transfusion was unnecessary in 179 of the 279 postpartum women (64.1%). If this scoring system is used to determine which patients should be transfused, unnecessary transfusions and their related risks and complications will be prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The pregnancy‐modified ISTH score was calculated based on a population of 24 646 pregnancies without and 87 with DIC (n = 24 693), had a 96% specificity, 36 and in an independent study attained a sensitivity of 78% and a specificity of 97% 45 . This modified score has proven useful for the identification of patients at risk for obstetrical hemorrhage requiring blood product transfusion 36,46,47 and can be applied in COVID‐19–affected pregnancies.…”
Section: Covid‐19 Coagulopathies In Pregnancymentioning
confidence: 99%
“…The pregnancy‐modified ISTH score was calculated based on a population of 24 646 pregnancies without and 87 with DIC (n = 24 693), had a 96% specificity, 36 and in an independent study attained a sensitivity of 78% and a specificity of 97% 45 . This modified score has proven useful for the identification of patients at risk for obstetrical hemorrhage requiring blood product transfusion 36,46,47 and can be applied in COVID‐19–affected pregnancies.…”
Section: Covid‐19 Coagulopathies In Pregnancymentioning
confidence: 99%
“…The activities of coagulation factors I, II, V, VII and X in plasma can be reflected by PT and TT. We found that PT and TT were significantly prolonged in the PPH after CD group, indicating impaired coagulation in the study group compared to the control group, which may be associated with massive hemorrhage 53 .…”
Section: Discussionmentioning
confidence: 66%
“… 135 Moreover, a retrospective analysis of blood product transfusion requirements in patients with PPH revealed that according to the pregnancy specific DIC score, blood transfusion was unnecessary in 179 of the 279 postpartum women (64.1%) suggesting that its use may prevent unnecessary transfusions and their related risks and complications. 136 Recently, Clark et al, 137 suggested an additional modified version of the ISTH DIC score. Erez et al 138 tested the performance of this suggested scoring system on their cohort and found that this score had 14.9% sensitivity, 99.9% specificity, and a LR+ score of 14.9.…”
Section: Diagnosis Of Dic In Pregnancy: Clinical Definitions Laboratory Findings and Scoring Systemsmentioning
confidence: 99%